2015
DOI: 10.1111/exd.12660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial peptides and cytokine production in primary keratinocyte cell culture from healthy and atopic beagles

Abstract: Increased secretion of antimicrobial peptides and cytokines is present in atopic skin. The purpose of this study was to compare the production of b-defensin (cBD)3-like, cathelicidin (cCath) and cytokines in atopic and healthy canine keratinocytes. Seven atopic house dust mites (HDMs) sensitive and five healthy age-matched beagles were used. Keratinocytes were stimulated for 24 h, and the supernatant was collected. A significantly higher production of cBD3-like was present at baseline in atopic compared with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Substances that increase TGF-β secretion by sublingual epithelial cells would therefore be interesting candidates for use as adjuvants during SLIT. While production of IL-6 and IL-10 has been observed in other types of epithelial cells (57)(58)(59)(60)(61)(62)(63), no secretion of these cytokines was detected for canine sublingual epithelial cells by ELISA or RNA sequencing. Furthermore, proallergenic mediators associated with the epithelium, TSLP, IL-25, and IL-33 (4,64) and the proinflammatory cytokines IL-1α and IL-1β were not expressed by canine sublingual epithelial cells.…”
Section: Figure 3 |mentioning
confidence: 81%
“…Substances that increase TGF-β secretion by sublingual epithelial cells would therefore be interesting candidates for use as adjuvants during SLIT. While production of IL-6 and IL-10 has been observed in other types of epithelial cells (57)(58)(59)(60)(61)(62)(63), no secretion of these cytokines was detected for canine sublingual epithelial cells by ELISA or RNA sequencing. Furthermore, proallergenic mediators associated with the epithelium, TSLP, IL-25, and IL-33 (4,64) and the proinflammatory cytokines IL-1α and IL-1β were not expressed by canine sublingual epithelial cells.…”
Section: Figure 3 |mentioning
confidence: 81%
“…Some recent in vitro studies have shown the involvement of AMP in AD in both human beings and dogs 57 58 . In human beings, the synthesis of AMPs is increased under the influence of vitamin D 20 and decreased in vitamin D deficiency 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The AMP levels present in the skin washes of atopic and healthy dogs were measured using either a commercially available (S100A8, S100A9 and S100A12 – Neoscientific; Woburn, MA, USA) or in‐house (cBD3‐like/cBD122 and cCath) previously validated, canine‐specific competitive inhibition ELISAs . To normalize the values of each AMP, the amount of total protein present in the skin wash was also determined using a commercially available kit (Micro BCA™ Protein Assay Kit, ThermoFischer Scientific; Grand Island, NY, USA) following the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The most commonly studied AMPs have been identified primarily in epithelial tissues, and include β‐defensins (BDs), cathelicidin (Cath) and S100A peptides . Human and canine keratinocytes have been demonstrated to produce AMPs, among others, BDs, Cath and S100A peptides …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation